Performance evaluation measurement of image steganography techniques with analysis of LSB based on variation image formats - Hashim, Mohammed Mahdi; Rahim, Mohd Shafry Mohd; Johi, Fadil Abass; Taha, Mustafa Sabah; Hamad, Hassan Salman (International Journal of Engineering and Technology, 2018)
Recently, Steganography is an outstanding research area which used for data protection from unauthorized access. Steganography is defined as the art and science of covert information in plain sight in various media sources such as text, images, audio, video, network channel etc. so, as to not stimulate any suspicion; while steganalysis is the science of attacking the steganographic system to reveal the secret message. This research clarifies the diverse showing the evaluation factors based on image steganographic algorithms. The effectiveness of a ste-ganographic is rated to three main parameters, payload capacity, image quality measure and security measure. This study is focused on im-age steganographic which is most popular in in steganographic branches. Generally, the Least significant bit is major efficient approach utilized to embed the secret message. In addition, this paper has more detail knowledge based on Least significant bit LSB within various Images formats. All metrics are illustrated in this study with arithmetical equations while some important trends are discussed also at the end of the paper.